Long-Term Effects of Adverse Maternal Care on Hypothalamic–Pituitary–Adrenal (HPA) Axis Function of Juvenile and Adolescent Macaques - Kai McCormack; Sara Bramlett; Elyse L. Morin; Erin R. Siebert; Dora Guzman; Brittany Howell; Mar M. Sanchez (Biology)
Early life adversity (ELA) is a known risk factor for psychopathology, including stress-related anxiety and depressive disorders. The underlying mechanisms and developmental changes remain poorly understood. A likely underpinning is the impact of ELA on the development of stress response systems, including the hypothalamic–pituitary–adrenal (HPA) axis. Our group studied a translational ELA model of spontaneous infant maltreatment by the mother in rhesus macaques, where we used a cross-fostering design to randomly assign infant macaques to either Control or Maltreating (MALT) foster mothers at birth to examine the impact of adverse caregiving on the development of the HPA axis, while controlling for the confounding effects of heritable and prenatal factors. We previously reported higher levels of plasma and hair cortisol (CORT) across the first 6 postnatal months (equivalent to the first 2 years of life in humans) in the MALT than in the Control infants. Here, we followed the same cohort of infants longitudinally to assess the long-term developmental impact of this adverse experience on HPA axis function during the juvenile (12, 18 months) and late adolescent (~5 years) periods. For this, we collected measurements of diurnal CORT rhythm and glucocorticoid negative feedback using the dexamethasone suppression test (DST). At 12 months, we found higher diurnal CORT secretion in MALT females compared to Control females, and impaired negative feedback in response to the DST in both sexes in the MALT group. However, ELA group differences in the HPA axis function disappeared by 18 months and late adolescence, while sex differences in diurnal CORT rhythm emerged or became stronger. These results suggest that infant maltreatment causes dysregulation of the HPA axis during the first year of life, with HPA axis function normalizing later, during the pre-pubertal juvenile period and adolescence. This suggests that the impact of maltreatment on HPA axis function may be transient, at least if the adverse experience stops. Our findings are consistent with human evidence of recalibration/normalization of HPA axis function during adolescence in children that switch from adverse/deprived environments to supportive adoptive families. This research has broad implications regarding the biological processes that translate ELA to psychopathology during development and the pathways to resiliency.